IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH ROLE PLAY - Nurbaya, Siti; Salam, Urai; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract:This research is designed as a research on improving students? speaking ability in class to the second semester of tenth grade class B students of MAN 2 Filial Pontianak. The purpose of the research is to improve students? ability in speaking of expression of happiness by applying role play technique. The method of this research was classroom action research. It was conducted in three cycles. The subjects of this research were 35 students at the second semester of the tenth grade students of MAN 2 Filial Pontianak in academic year 2014/2015. After collecting the data, the writer found that improving students? ability in expression of happiness through Role Play technique is work well. Based on the data analysis, the result of the research was progress. It is showed that the students? mean score for speaking ability in expression of happiness improved. It could be seen on data analysis result from each cycle (53, 11 on cycle 1, 67, 51 on cycle 2, and 75, 85 on cycle 3). Even students fulfilled KKM (standard achievement) on cycle 2, however, the teacher and collaborator decide to do 3 cycle to make sure that using role play was really suitable for students? speaking ability improvement. Based on the result of the data analysis, the writer took a conclusion that Role Play technique is work well and can be applied.   Keywords: Role Play Technique, Classroom Action Research, Speaking Ability.   Abstrak: Penelitian ini dilaksanakan sebagai upaya meningkatkan kemampuan berbicara siswa kelas X semester 2 MAN 2 Filial Pontianak.Tujuan penelitian ini adalah untuk menunjukan kemampuan siswa dalam berbicara dengan menerapkan teknik bermain peran, dimana siswa berperan menjadi rang lain saat pertunjukan di depan kelas dimulai. Metode penelitian ini adalah Penelitian Tindakan kelas dan dilakukan dalam 3 siklus dengan prosedur yaitu, persiapan, bertindak, obserpasi, dan refleksi terhadap siswa kelas X semester 2 Man 2 Filial Pontianak tahun akademik 2014/2015 dan jumlah siswa adalah 35 orang. Data tes menunjukan bahwa rata-rata perolehan nilai siswa pada siklus 1 yaitu 53, 11, sikuls 2 yaitu 67,51, dan siklus 3 yaitu 75,85, itu berarti kategori yang cukup baik. Berdasarkan data diatas dapat disimpulkan bahawa dalam pengguanaan teknik bermain peran di kelas adalah baik dan dapat digunakan.   Kata Kunci:Teknik Bermain Peran, Penelitian Tindakan Kelas, Kemampuan Berbicara.